Avaliação do uso terapêutico do extrato de Lafoensia pacari St. Hil. Mangava-Brava na erradicação do Helicobacter pylori: Ensaio Clínico Randomizado Duplo Cego - Menezes, Valfredo da Mota [UNIFESP] (2006)
Background: The eradication of Helicobacter pylori is easily achieved by combining antisecretory agents and antibiotics; however, the cost of these associations is very high for the population of Third World countries, where the prevalence of the infection is even higher and leads to markedly reduced treatment effectiveness. We tested a plant (Lafoensia pacari) that is used in the central region of Brazil. According to previous studies, this plant has high concentrations of ellagic acid, which presents gastric antisecretory and antibacterial actions. Material and Methods: 100 dyspeptic, urease-positive patients were randomized to receive 500mg of methanolic extract of L. pacari (n= 55) or placebo (n= 45), for 14 days, in a double-blind clinical trial. The main variables assessed were the eradication of H. pylori eight weeks after the intervention and complete symptom relief at the end of the treatment. Results: The exams (urease and histology) showed persistence of H. pylori in 100% of participants. Complete symptom relief was experienced by 42.5% of patients (95% CI: 29.4-55.8) in the intervention group and by 21% (95% CI: 8.8-33.1) in the control group, p=0.020. The side effects were minimum and similar in both groups. Conclusions: The extract of L. pacari as a single agent was not effective to eradicate H. pylori. However, it was well tolerated and many participants reported relief of symptoms. Future studies may test the agent using larger doses and longer periods, in monotherapy or in combination with antibiotics.